Race and COVID-19 among Social Workers in Health Settings: Physical, Mental Health, Personal Protective Equipment, and Financial Stressors. Issue 2 (3rd March 2023) - Zerden, Lisa de Saxe; Ross, Abigail M; Cederbaum, Julie; Guan, Ting; Zelnick, Jennifer; Ruth, Betty J
Abstract: Social work is an essential workforce integral to the United States' public health infrastructure and response to COVID-19. To understand stressors among frontline social workers during COVID-19, a cross-sectional study of U.S-based social workers ( N = 1, 407) in health settings was collected (in June through August 2020). Differences in outcome domains (health, mental health, personal protective equipment [PPE] access, financial stress) were examined by workers' demographics and setting. Ordinal logistic, multinomial, and linear regressions were conducted. Participants reported moderate or severe physical (57.3 percent) and mental (58.3 percent) health concerns; 39.3 percent expressed PPE access concerns. Social workers of color were more likely to report significantly higher levels of concern across all domains. Those identifying as Black, American Indian/Alaska Native (AIAN), Asian American/Pacific Islander (AAPI), multiracial, or Hispanic/Latinx were over 50 percent more likely to experience either moderate or severe physical health concerns, 60 percent more likely to report severe mental health concerns, and over 30 percent more likely to report moderate PPE access concerns. The linear regression model was significantly associated with higher levels of financial stress for social workers of color. COVID-19 has exposed racial and social injustices that that hold true for social workers in health settings. Improved social systems are critical not just for those impacted by COVID-19, but also for the protection and sustainability of the current and future workforce responding to COVID-19.